Progressive Web Apps: Pengembangan dan Studi Penerimaan pada Mahasiswa Indonesia Menggunakan Scrum dan UTAUT - Herman, Herman; Frederick, Frederick (LPPM STT Terpadu Nurul Fikri, 2023)
Currently, the usage of mobile applications and the total activity on mobile phones through web browsing or native applications is very high. Most users use native mobile apps to browse the content of specific industries. Another way to do so is through a web browser. However, both have limitations. In web applications, users' experience is not that great compared to native applications. On mobile native applications, it requires higher development costs to ensure the app can be accessed across multiple platforms. To solve this problem, Google launched progressive web apps as an alternative, where progressive web apps can be accessed through different platforms, saving development costs but still providing a user experience almost the same as native apps. The focus of this research is to develop a progressive web app with React.js using the scrum method and also to research user acceptance of progressive web apps through qualitative methods/interviews based on the UTAUT research model to general students and lecturers of computer science. The result of this research, based on UTAUT points, shows positive responses toward accepting progressive web apps. Then with the rapid development of the web and browsers, progressive web apps will potentially have a promising future. With this research, it is hoped that can bring benefits to the decision to use the progressive web apps, become a reference for the next research, and increase the knowledge of the public and readers about the progressive web apps.